2007
DOI: 10.1002/micr.20436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various protocols of ischemic preconditioning on rat tram flaps

Abstract: We used rat transverse rectus abdominis musculocutaneous (TRAM) flaps to investigate whether the ischemic cycle duration and number of cycles influenced the effectiveness of ischemic preconditioning (IPC). First, the animals were divided into one control group and four treatment groups. Controls received no preconditioning; flaps with IPC were treated by two cycles of pedicel clamping and reperfusion for either 5 or 10 min. Then the best of IPC protocols in first part was selected, and flaps were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In another study where three cycles of ischaemia and reperfusion were applied, the authors reported that the survival rate of the flaps increased with 16% [16]. Ischaemic preconditioning could improve the viability of musculocutaneous flaps and two and three cycles of ischaemic preconditioning with a 10/5-minute combination were more effective than a single cycle of ischaemic preconditioning [17]. Furthermore, the results of a recently published study have suggested that the optimal time for ischaemic preconditioning is 3 days before the flap elevation in a flap operation [18].…”
Section: Discussionmentioning
confidence: 97%
“…In another study where three cycles of ischaemia and reperfusion were applied, the authors reported that the survival rate of the flaps increased with 16% [16]. Ischaemic preconditioning could improve the viability of musculocutaneous flaps and two and three cycles of ischaemic preconditioning with a 10/5-minute combination were more effective than a single cycle of ischaemic preconditioning [17]. Furthermore, the results of a recently published study have suggested that the optimal time for ischaemic preconditioning is 3 days before the flap elevation in a flap operation [18].…”
Section: Discussionmentioning
confidence: 97%
“…I/R injury is classified as either primary or secondary in the context of plastic surgery. In free flap surgery, the time between removal of the flap from the donor area and commencement of reperfusion is termed “primary ischemia,” and ischemia developing after a flap is placed is termed “secondary ischemia.” The latter type of ischemia is of greater concern in flap surgery, and the effect of ischemic conditioning on I/R injury has been investigated previously . Only a single report on I/R injury has appeared; the ischemia spared the three perforators of a deep inferior epigastric perforator flap.…”
Section: Discussionmentioning
confidence: 99%
“…21 The latter type of ischemia is of greater concern in flap surgery, and the effect of ischemic conditioning on I/R injury has been investigated previously. 1,[19][20][21][22] Only a single report on I/R injury has appeared; the ischemia spared the three perforators of a deep inferior epigastric perforator flap. 23 In this study, we used cranial epigastric perforator flap that was described by Okşar et al firstly, 17 then showed as a true perforator flap model by Hallock and Rice.…”
Section: Discussionmentioning
confidence: 99%
“…10 One study demonstrated that vascular delay in flaps improved survival 2.5-3 times over the control. 11…”
Section: Discussion Vascular Delay -Reconstructive Surgery Perspectivementioning
confidence: 99%